2017
DOI: 10.2139/ssrn.2937135
|View full text |Cite
|
Sign up to set email alerts
|

Does the More Educated Utilize More Health Care Services? Evidence from Vietnam Using a Regression Discontinuity Design

Abstract: In 1991 Vietnam implemented a compulsory schooling reform that provides this paper a natural experiment to estimate the causal effect of education on health care utilization measured by the probability of doctor visit, the frequency of doctor visit and per visit out-of-pocket expenditure with a regression discontinuity design. The paper finds that schooling induces considerable impacts on health care utilization although the signs of the impacts changes with specific types of health care service examined. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Equally importantly, the F-statistics of the excluded instrument in the first-stage is approximately 76.06, suggesting that the reform is satisfactorily associated with schooling years the endogenous variable in this study (Staiger and Stock 1997). The significant positive link between the reform and educational outcome in this study is completely consistent with the findings from previous studies for Vietnam implemented by Dang (2017aDang ( , 2017b) that also use the same reform as an instrument for exogenous variations on years of schooling.…”
Section: Baseline Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Equally importantly, the F-statistics of the excluded instrument in the first-stage is approximately 76.06, suggesting that the reform is satisfactorily associated with schooling years the endogenous variable in this study (Staiger and Stock 1997). The significant positive link between the reform and educational outcome in this study is completely consistent with the findings from previous studies for Vietnam implemented by Dang (2017aDang ( , 2017b) that also use the same reform as an instrument for exogenous variations on years of schooling.…”
Section: Baseline Resultssupporting
confidence: 87%
“…Furthermore, reduced-form estimates illustrate that workers exposed to the reform are more likely to achieve non-wage benefits than those who were out of the reform, in particular for monetary payments for public holidays by 11.4 percentage points, monetary employee benefits by 8.8 percentage points, annual paid leave by 13.8 percentage points and firm-provided social insurance by 13 percentage points. Interestingly, it is obvious that the impact of schooling is larger for fringe 2 The 1991 compulsory schooling reform in Vietnam was used as an instrument for exogeneous changes in schooling from some recent studies related to the causal effects of schooling in health care utilization or political outcomes for examples Dang (2017aDang ( , 2017b.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the study revealed that education led to an increase in inpatient utilization within the public health sector, but it also resulted in a decrease in outpatient utilization in both the public and private health sectors (Dang, 2018).…”
Section: Literature Reviewmentioning
confidence: 92%
“…The issue of inequality in inpatient and outpatient medical care in Vietnam has received considerable attention from numerous authors. Dang (2018) conducted an analysis using a regression discontinuity design to investigate the causal relationship between education and health care utilization. The findings indicated a statistically significant impact of education on health care utilization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, this study's analysis examines these two outcomes for both inpatient and outpatient services at both public and private health sectors. It is useful to devide health care services into two types inpatient and outpatient services because these two services are key types of medical care services within the health care system and they also reflect various quality of services provided (Dang 2017).…”
Section: Introductionmentioning
confidence: 99%